1975
DOI: 10.1210/endo-97-6-1593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ACTH, α-MSH, and β-Lipotropin on Calcium and Phosphorus Metabolism in the Rabbit

Abstract: Studies were undertaken to investigate the effects of synthetic 1-24 adrenocorticotropin (ACTH), bovine alpha melanocyte-stimulating hormone (alpha-MSH), and ovine beta lipotropin (beta-LPH) on plasma calcium and phosphate in rabbits. Equimolar concentrations of these hormones were infused intravenously in intact and thyroidectomized animals. In addition, ACTH was similarly administered to adrenalectomized rabbits. ACTH, alpha-MSH, and beta-LPH all lowered plasma calcium and raised plasma phosphate. These chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Six years later, Akgün & Rudman (1969) corroborated this work and showed that a-MSH gave a similar result. More recently, Gildersleeve et al (1975) injected rabbits with these hormones (the molecules of which shared the same peptide sequence); they not only confirmed the presence of hypocalcaemia but also revealed the presence of hypophosphataemia. Chrétien et al (1973) also found hypocalcaemia with LPH but observed normal blood calcium in previously thyroidectomized rabbits injected with this hormone.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Six years later, Akgün & Rudman (1969) corroborated this work and showed that a-MSH gave a similar result. More recently, Gildersleeve et al (1975) injected rabbits with these hormones (the molecules of which shared the same peptide sequence); they not only confirmed the presence of hypocalcaemia but also revealed the presence of hypophosphataemia. Chrétien et al (1973) also found hypocalcaemia with LPH but observed normal blood calcium in previously thyroidectomized rabbits injected with this hormone.…”
Section: Resultsmentioning
confidence: 86%
“…which they attributed to the release of calcitonin from the thyroid gland. However, Gildersleeve, Pearson, Baghdiantz & Foster (1975) were unable to show the mediation of the thyroid gland in the hypocalcaemia occurring after administration of ACTH, a-MSH and ß-LPH. Moreover, their findings indicate that ACTH does not induce hypocalcaemia through stimulating the secretory activity of the adrenal cortex.…”
Section: Introductionmentioning
confidence: 86%